Characterizing the influence of anthropogenic emissions and transport variability on sulfate aerosol concentrations at Mauna Loa Observatory - Potter, Lauren E., author; Kreidenweis, Sonia, advisor; Maloney, Eric, committee member; Farmer, Delphine, committee member; Cooley, Daniel, committee member (Colorado State University. Libraries, 2013)
Sulfate aerosol in the atmosphere has substantial impacts on human health and environmental quality. Most notably, atmospheric sulfate has the potential to modify the earth's climate system through both direct and indirect radiative forcing mechanisms (Meehl et al., 2007). Emissions of sulfur dioxide, the primary precursor of sulfate aerosol, are now globally dominated by anthropogenic sources as a result of widespread fossil fuel combustion. Economic development in Asian countries since 1990 has contributed considerably to atmospheric sulfur loading, particularly China, which currently emits approximately 1/3 of global anthropogenic SO2 (Klimont et al., 2013). Observational and modeling studies have confirmed that anthropogenic pollutants from Asian sources can be transported long distances with important implications for future air quality and global climate change. Located in the remote Pacific Ocean (19.54°N, 155.58°W) at an elevation of 3.4 kilometers above sea level, Mauna Loa Observatory (MLO) is an ideal measurement site for ground-based, free tropospheric observations and is well situated to experience influence from springtime Asian outflow. This study makes use of a 14-year data set of aerosol ionic composition, obtained at MLO by the University of Hawaii at Manoa. Daily filter samples of total aerosol concentrations were made during nighttime downslope (free-tropospheric) transport conditions, from 1995 to 2008, and were analyzed for aerosol-phase concentrations of the following species: nitrate (NO3-), sulfate (SO42-), methanesulfonate (MSA), chloride (Cl-), oxalate, sodium (Na+), ammonium (NH4+), potassium (K+), magnesium (Mg2+), and calcium (Ca2+). An understanding of the factors controlling seasonal and interannual variations in aerosol speciation and concentrations at this site is complicated by the relatively short lifetimes of aerosols, compared with greenhouse gases which have also been sampled over long time periods at MLO. Aerosol filter data were supplemented with observations of gaseous radon (Rn222) and carbon monoxide (CO), used as tracers of long distance continental influence. Our study applied trajectory analysis and multiple linear regression to interpret the relative roles of aerosol precursor emissions and large-scale transport characteristics on observed MLO sulfate aerosol variability. We conclude that observed sulfate aerosol at MLO likely originated from a combination of anthropogenic, volcanic, and biogenic sources that varied seasonally and from year to year. Analysis of chemical continental tracer concentrations and HYSPLIT back trajectories suggests that non-negligible long distance influence from either the Asian or North American continents can be detected at MLO during all seasons although large interannual variability was observed. Possible influence of circulation changes in the Pacific Basin related to the El Niño-Southern Oscillation were found to be both species and seasonally dependent. We further found an increasing trend in monthly mean sulfate aerosol concentrations at MLO of 4.8% (7.3 ng m-3) per year during 1995-2008, significant at the 95% confidence level. Multiple linear regression results suggest that the observed trend in sulfate concentrations at MLO cannot reasonably be explained by variations in meteorology and transport efficiency alone. An increasing sulfate trend of 5.8 ng m-3 per year, statistically significant at the 90% confidence level, was found to be associated with the variable representing East Asian SO2 emissions. The results of this study provide evidence that MLO sulfate aerosol observations during 1995-2008 reflect, in part, recent trends in anthropogenic SO2 emissions which are superimposed onto the natural meteorological variability affecting transport efficiency.
Keywords: aerosol; transport; sulfate; Mauna Loa Observatory